Security In E-Commerce - A Review Of Legislations, Cases, Guidelines, Policies And Regulations - Oh, Alan Kim Lok (2005)
This research reviews available legislations, cases, guidelines, policies and regulations formed by goverments to combat security issues in e-commerce. The following issues will be examined with reference to the purpose of this study: E-commerce policies, computer crimes, electronic privacy and authentication & encryption.